2020
DOI: 10.3389/fendo.2019.00941
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Gut Microbiota With Idiopathic Central Precocious Puberty in Girls

Abstract: Idiopathic central precocious puberty (ICPP) is a relatively common condition in preadolescent girls, and its pathogenesis remains to be uncovered. A variety of studies have highlighted the association of gut microbiota (GM) with endocrine diseases, such as obesity, which is commonly associated with ICPP. However, the relationship between GM and ICPP remains unexplored. Feces samples were collected from 25 girls with ICPP (ICPP group) and 23 healthy girls (Control group). We applied 16S rDNA sequencing to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 48 publications
(46 reference statements)
1
46
0
Order By: Relevance
“…It has been reported that the abundance of gut Coprobacillus was enriched in BALB/c male mice [ 16 ], suggesting a possibility that the abundance of gut Coprobacillus could be affected by sex hormon e . Dong G reported that gut Coprococcus was enriched in girls with idiopathic central precocious puberty [ 17 ]. All microbes in genera Coprococcus promote SCFAs production [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the abundance of gut Coprobacillus was enriched in BALB/c male mice [ 16 ], suggesting a possibility that the abundance of gut Coprobacillus could be affected by sex hormon e . Dong G reported that gut Coprococcus was enriched in girls with idiopathic central precocious puberty [ 17 ]. All microbes in genera Coprococcus promote SCFAs production [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the proportion of the genus Anaerotruncus increased gradually with the puberty stages, and the proportion of the genus Coprococcus rst increased, and then decreased to a similar proportion with the early puberty group, suggesting that the two genera are closely associated with puberty. It has been reported that gut Coprococcus was enriched in girls with idiopathic central precocious puberty (20). All microbes in genera Coprococcus promote SCFAs production (21)(22)(23).…”
Section: Discussionmentioning
confidence: 96%
“…All microbes in genera Coprococcus promote SCFAs production (21)(22)(23). Therefore, it is plausible that SCFAs-producing bacteria are increased in pubertal subjects to promote the expression of the leptin gene, which in turn activate the hypothalamic-pituitary-gonad axis, and lead to the onset of puberty (20).…”
Section: Discussionmentioning
confidence: 99%